2020
DOI: 10.1111/crj.13272
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, severity and tolerability of pneumothorax following low‐dose CT‐guided lung biopsy in different severities of COPD

Abstract: Background The feasibility of pneumothorax following low‐dose CT‐guided puncture lung biopsy in different severities of COPD has not been reported. Methods The data of the patients with pulmonary lesion who underwent low‐dose CT‐guided lung biopsy by one experienced operator in our hospital from January 1st to September 30th in 2019 were retrospectively collected. They were divided into COPD group and non‐COPD group. The risk factors, incidence and severity of pneumothorax with the severity of COPD and changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In this study, complications of multislice spiral CT-guided lung biopsy were observed, and the results showed that there was no statistical significance in the incidence of pneumothorax in groups of different sizes of pulmonary nodules. According to relevant reports, the incidence of pneumothorax of CT-guided transthoracic lung biopsy is 15.4%~42.0%, only 4.3%~7.3% patients need thoracic catheter drainage, and the incidence of hemoptysis is 0.5%~14.4%, most of which do not need intervention [ 20 , 21 ]. The common risk factors of pneumothorax include long puncture path, multiple crossing of pleura, and small lesion [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, complications of multislice spiral CT-guided lung biopsy were observed, and the results showed that there was no statistical significance in the incidence of pneumothorax in groups of different sizes of pulmonary nodules. According to relevant reports, the incidence of pneumothorax of CT-guided transthoracic lung biopsy is 15.4%~42.0%, only 4.3%~7.3% patients need thoracic catheter drainage, and the incidence of hemoptysis is 0.5%~14.4%, most of which do not need intervention [ 20 , 21 ]. The common risk factors of pneumothorax include long puncture path, multiple crossing of pleura, and small lesion [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have focused on the implementation of ULD protocols during percutaneous lung biopsies under CT guidance [21][22][23][24][25][26][27]. One of the most robust prospective randomised studies was published by Fu et al, demonstrating a ten-fold decrease of mean DLP (36.0 ± 14.1 mGy cm vs. 361.8 ± 108.0 mGy cm, p < 0.001) and effective dose (0.5 ± 0.2 mSv vs. 5.1 ± 1.5 mSv, p < 0.001) with comparable diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The convolutional neural network model (CNN) [ 19 ] and residual network model (ResNet) [ 20 ] were introduced for comparison with the improved DRCNN model that is proposed in this research.…”
Section: Methodsmentioning
confidence: 99%